2016
DOI: 10.1590/1982-0216201618524715
|View full text |Cite
|
Sign up to set email alerts
|

O efeito da eletroestimulação neuromuscular na contração da musculatura supra-hióidea durante a deglutição de indivíduos com disfagia

Abstract: Purpose: the purpose of this study is to verify the effect of Neuromuscular Electrical Stimulation on the suprahyoid muscle activity during swallowing, in post stroke subjects, with oropharyngeal dysphagia. Methods: participated eight post-stroke subjects with dysphagia, male and female, referred to speech--language therapy to early swallowing rehabilitation. Before the first rehabilitation session, the patient´s muscular electrical activity of suprahyoid muscle was measured using Surface Electromyography Biof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…EMG has been used to assess the activity of swallowing muscles, both in people with normal swallowing and in those with swallowing disorders 29 . When studying the electromyographic activity of individuals with and without CD, we observed that patients with CD had lower activity than those without CD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMG has been used to assess the activity of swallowing muscles, both in people with normal swallowing and in those with swallowing disorders 29 . When studying the electromyographic activity of individuals with and without CD, we observed that patients with CD had lower activity than those without CD.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to consider that the amplitude of the electrical activity, recorded by EMG in this study, is one of the important factors in the relationship between muscle recruitment and electrical activity 29 . However, amplitude variations in EMG are not only due to biological causes, but also due to technical factors such as skin/electrode impedance, anatomical location of recording electrodes, differences in muscle size between individuals, and temperature 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Para tratar la disfagia orofaríngea se requiere un abordaje de rehabilitación, entre diversas técnicas tenemos la modalidad terapéutica de electroestimulación neuromuscular, dicha intervención comprende la aplicación de electrodos en la región del cuello provocando la estimulación de contracciones en los músculos responsables de la deglución con el fin de potenciar la funcionalidad de dicha musculatura: Como ser restablecer las condiciones mínimas de contracción muscular, funcionalidad muscular, propiocepción y cinestesia vinculada directa e indirectamente a la movilidad laríngea en el proceso deglutorio. Existe un acuerdo literario a considerar que resultados son en su mayoría efectivos si se aplica electroterapia en combinación con ejercicios de compensación enfocados en la rehabilitación de disfagia (12)(13)(14)(15).…”
Section: Introductionunclassified